Distinct performance profiles on the Brixton test in frontotemporal dementia. Issue 2 (15th October 2020) - Rao, Sulakshana P.; Nandi, Ranita; Dutt, Aparna; Kapur, Narinder; Harris, Jennifer M.; Thompson, Jennifer C.; Snowden, Julie S.
Abstract : The Brixton Spatial Anticipation Test is a well‐established test of executive function that evaluates the capacity to abstract, follow, and switch rules. There has been remarkably little systematic analysis of Brixton test performance in the prototypical neurodegenerative disorder of the frontal lobes: behavioural variant frontotemporal dementia (bvFTD) or evaluation of the test's ability to distinguish frontal from temporal lobe degenerative disease. We carried out a quantitative and qualitative analysis of Brixton performance in 76 patients with bvFTD and 34 with semantic dementia (SD) associated with temporal lobe degeneration. The groups were matched for demographic variables and illness duration. The bvFTD group performed significantly more poorly ( U = 348, p < .0001, r = .58), 53% of patients scoring in the poor–impaired range compared with 6% of SD patients. Whereas bvFTD patients showed problems in rule acquisition and switching, SD patients did not, despite their impaired conceptual knowledge. Error analysis revealed more frequent perseverative errors in bvFTD, particularly responses unconnected to the stimulus, as well as random responses. Stimulus‐bound errors were rare. Within the bvFTD group, there was variation in performance profile, which could not be explained by demographic, neurological, or genetic factors. The findings demonstrate sensitivity and specificity of the Brixton test in identifying frontal lobe degenerative disease and highlight the clinical value of qualitative analysis of test performance. From a theoretical perspective, the findings provide evidence that semantic knowledge and the capacity to acquire rules are dissociable. Moreover, they exemplify the separable functional contributions to executive performance.